Grassroot NGOs and Political Reform in Thailand: Democracy behind Civil Society - Naruemon Thabchumpon (The Copenhagen Journal of Asian Studies, 1998)
This article argues that behind the concept of civil society is a real opportunity for populist forces to drive democracy forward. In Thailand, the participatory role of non-governmental organisations, particularly at grassroots level, is very important. By advocating people's participation and empowerment, grassroots NGOs may be in a position to expand notions of democracy, from mere parliamentarism to genuine participatory democracy. In the Thai case, however, success will depend upon whether the grassroots non-governmental organisations (GNGOs) are able to establish a linkage between 'elite-urban' and 'rural-popular' elements in Thai civil society. The key question is whether these organisations are able to democratise Thai civil society and create an enhanced form of participatory democracy.